2019
DOI: 10.1038/s41388-019-1046-5
|View full text |Cite|
|
Sign up to set email alerts
|

HUNK phosphorylates EGFR to regulate breast cancer metastasis

Abstract: Epidermal growth factor receptor (EGFR) is commonly over-expressed in metastatic breast cancer yet metastatic breast cancer is generally resistant to anti-EGFR therapies, and the mechanism for resistance to EGFR inhibitors in this setting is not fully understood. Hormonally up-regulated neu-associated kinase (HUNK) kinase is up-regulated in aggressive breast cancers and is thought to play a role in breast cancer metastasis. However, no studies have been conducted to examine a relationship between EGFR and HUNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…EGFR has been used as an effective therapeutic target for tyrosine kinase inhibitors in lung and pancreatic cancers 32,33 . Furthermore, the activation of EGFR to promote tumor metastasis has been widely proven in various tumors [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…EGFR has been used as an effective therapeutic target for tyrosine kinase inhibitors in lung and pancreatic cancers 32,33 . Furthermore, the activation of EGFR to promote tumor metastasis has been widely proven in various tumors [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…The growth factor FGF18 regulates development of the neural system, specifically the midbrain structure [46]. Finally, HUNK is a serine/threonine kinase, which was recently shown to be associated with control of expression of E-cadherin [47], a molecule that can act as a receptor for pathogens [48]. We identified a 1-bp deletion in the 3′UTR region of the HUNK gene, which was fixed in the line with a low V E of LS and absent in the line with a high V E of LS.…”
Section: Discussionmentioning
confidence: 99%
“…However, our conclusions from the use of the MDA MB 468 cell line differed from this particular study. We showed that shRNA depletion of HUNK reduced cell migration and invasion compared to cells expressing a non-functional shRNA control, whereas the prior study showed that overexpression of HUNK suppresses migration and invasion [10,12]. While the use of individual reagents and techniques could certainly be attributed to the differences in results, another possibility is that exogenous HUNK could act as a dominant negative toward endogenous protein.…”
mentioning
confidence: 71%
“…al., our findings showed that HUNK is pro-metastatic. Separate from the two prior studies, our study showed that HUNK phosphorylates the epidermal growth factor receptor (EGFR) at threonine (T) 654 to regulate breast cancer metastasis, providing a discrete HUNK-kinase dependent mechanism for this process [10]. Our study used the 4T1 mouse mammary tumor cell line as well as two human basal breast cancer cell lines, the MDA MB 468 and BT20 model.…”
mentioning
confidence: 89%
See 1 more Smart Citation